4-Hydroxy-2-Nonenal, Indused Nitric Oxide Synthase Statues in Hypertension Patients - Hammed, Ali D; Jawad, Alaa H; Saifullah, Perry H (Al-Nahrain Journal of Science, 2017)
The oxidative stress is one of the main cause for cardiovascular diseases (like Hypertension) also one of the results of these diseases. This study involved 56 subjects matched ages and sex divided into two groups; 28 hypertensive subject and 28 healthy subject as control group. The following analysis was done: 4-Hydroxy-2-nonenal (4HNE), Induced nitric oxide synthase (iNOS) and albumin. The results show that there is a significant increase in (4HNE) between patients group and control group. INOS was significantly higher in patients compared to controls while there were no significant difference found in albumin between patient and control group. The increase in 4HNE which is a product of lipid peroxidation is attributed to destruction in body cell caused by due to the increase in stress events. And the increase in iNOS because iNOS produces large amounts of NO as a defense mechanism in response to cytokines and is an important factor in the response of the body to attack by parasites, bacterial infection, and tumor growth. It has been concluded that is important nappy on ideal weight, because obesity considered main factors for heart disease and hardening of the arteries. There is a positive relationship between oxidation results from hypertension and their developments. The aim of this study was to investigate the relationship between of some oxidative stress markers and cardiovascular diseases